Effects on survival of loop diuretic dosing in ambulatory patients with chronic heart failure using a propensity score analysis. Issue 7 (13th June 2013) - Dini, F. L.; Ghio, S.; Klersy, C.; Rossi, A.; Simioniuc, A.; Scelsi, L.; Genta, F. T.; Cicoira, M.; Tavazzi, L.; Temporelli, P. L.
Summary Objective To ascertain whether increasing doses of orally administered furosemide are associated with impaired survival in outpatients with chronic heart failure (CHF) and left ventricular (LV) systolic dysfunction. Methods Transthoracic echo‐Doppler examination was carried out at baseline in 813 consecutive CHF outpatients with LV ejection fraction ≤ 45%. The total daily dose of furosemide was assessed for each patient. Chronic kidney disease (CKD) was defined by a glomerular filtration rate < 60 ml/min/1.73 m2. The end‐point was all‐cause mortality. To control the prognostic effect of furosemide for the propensity of using high doses of the drug, the Cox model was stratified by the propensity score, itself computed from a multivariable logistic model. Mean follow up was 44 months. Results After stratification for the propensity score, the risk of death increased linearly across quartiles of furosemide dose (HR 1.38, 95% CI 1.14–1.68, p < 0.001). A daily dose of 50 mg was identified as the best threshold value to predict a high risk of death within 3 years with an area under the ROC curve of 0.68 (95% CI 0.64–0.72). Increasing doses of furosemide were associated with an increased risk of death regardless of LV filling pattern, CKD and background therapy with ACE‐inhibitors or beta‐blockers. Conclusions In outpatients with CHF, after stratification for the propensity score, the risk of death increased linearly across quartiles of furosemide daily dose. A threshold furosemide dose of 50 mg was related with the worse outcome.